SEASONAL AND DAILY ACTIVITIES OF TWO SYNTOPIC PARTHENOGENETIC LIZARDS OF GENUS DAREVSKIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2014)
The patterns of seasonal and daily activities of two parthenogenetic species of lizards ($Darevskia~armeniaca,~D.~unisexualis$) sharing the same territories in the zone of hybridization in central region of Armenia demonstrate ecologically similar potential niches.
Keywords: parthenogenetic species, seasonal and daily activities